Time to pregnancy among Danish pharmacy assistants. - Schaumburg, Inger; Olsen, Jørn (Scandinavian Journal of Work, Environment & Health, 1989)
Time to pregnancy was studied as a parameter of couple fertility in a national cohort of all female members (less than 40 years) of the union of pharmacy assistants from 1979 to 1984. A total of 4 924 women were included in the study. Information on time to pregnancy and exposure was obtained by postal questionnaires in April 1985 (response rate 92%). Prolonged time to pregnancy according to occupation in production or a dispensary or in product control, bottling, and packing is presented, unexposed pharmacy assistants being used as referents. It was possible to use time to pregnancy in an occupational setting as 95% of the women were able to state their time to pregnancy and as 90% of all pregnancies were planned. No association was found between type of work or pharmacy and time to pregnancy, but pharmacy assistants exposed to antibiotics had a slightly increased risk of prolonged time to pregnancy.